The role of artificial intelligence in the uncertainty of the world Paul and Sophias abilities that challenge minds - Ahmad Afif, Ahmarofi (Pejabat Naib Canselor, 2021)
2020 is a year with unique figures and various events that rocked the world. Ranging from the devastating forest fires in Australia, the George Floyd riots in the United States, the deadly explosions in Beirut, Malaysia’s political unrest, to the COVID-19 pandemic disaster. These events make this world in a state of uncertainty to humans, the environment and the economy.